DECOMPOSITION AND BINDING ACTION OF A POLYSACCHARIDE FROM CHROMOBACTERIUM VIOLACEUM IN SOIL - Martin, J. P. (1963)
Martin, J. P. (University of California, Riverside) and S. J. Richards. Decomposition and binding action of a polysaccharide from Chromobacterium violaceum in soil. J. Bacteriol. 85:1288–1294. 1963.—The decomposition rate and binding effect in soil of a polysaccharide from Chromobacterium violaceum was compared with that of a variety of bacterial and plant polysaccharides and more complex organic residues. Most of the polysaccharides tested decomposed more readily than mature plant residues and fungus mycelium. The ease of decomposition varied, however, and polysaccharide from C. violaceum over a period of 1 month was more resistant than corn stalks, Rhodes grass, bean straw, and orange leaves. During the first week, it was as resistant to decay as pine needles. The C. violaceum polysaccharide was more effective in binding or aggregating the soil than all others tested. It also reduced the bulk density of Greenfield sandy loam and increased hydraulic conductivity in neutral soil.